(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The truths arising from the formation of museums, the systemic organization of archive work in museums in Azerbaijan, underscore the importance of paying attention to archival matters and fund collection in museums. The article raises the question of the importance of the museum and archive business in the context of the correct perception of the socio-political palette of each era. However, comparatively analyzed are similar and different features between the structure and activities of museums and archives. On the basis of the research, it is concluded that the museum, documenting the development of society, is not limited to taking objects from real life and turning them into museum items, but at the same time it ensures the perception of the stages of development of the society and the period to which it belongs. In any historical periods and conditions in the study of the object is important a systematic approach to it, based on a comprehensive study of documents. So, if research is being conducted around the twentieth century, then in this era the socially neutral principle of archival science was violated, since in the Soviet period this principle was replaced by the principle of communist party spirit. Key words: museum, archive, fund, collection, scientific research.